Altered dopamine ontogeny in the developmentally vitamin D deficient rat and its relevance to schizophrenia - Kesby, James P.; Cui, Xiaoying; Burne, Thomas H.; Eyles, Darryl W. (Frontiers in Cellular Neuroscience, 2013)
Schizophrenia is a heterogeneous group of disorders with unknown aetiology. Although abnormalities in multiple neurotransmitter systems have been linked to schizophrenia, alterations in dopamine neurotransmission remain central to the treatment of this disorder. Given that schizophrenia is considered a neurodevelopmental disorder we have hypothesised that abnormal dopamine signalling in the adult patient may result from altered dopamine signalling during foetal brain development. Environmental and genetic risk factors can be modelled in rodents to allow for the investigation of early neurodevelopmental pathogenesis that may lead to clues into the aetiology of schizophrenia. To address this we created an animal model of one such risk factor, developmental vitamin D (DVD) deficiency. DVD-deficient adult rats display an altered behavioural profile in response to dopamine releasing and blocking agents that are reminiscent of that seen in schizophrenia patients. Furthermore, developmental studies revealed that DVD deficiency also altered cell proliferation, apoptosis and neurotransmission across the embryonic brain. In particular, DVD deficiency reduces the expression of crucial dopaminergic specification factors and alters dopamine metabolism in the developing brain. We speculate such alterations in foetal brain development may change the trajectory of dopamine neuron ontogeny to induce the behavioural abnormalities observed in adult offspring. The widespread evidence that both dopaminergic and structural changes are present in people who develop schizophrenia prior to onset also suggest that early alterations in development are central to the disease. Taken together, early alterations in dopamine ontogeny may represent a core feature in the pathology of schizophrenia. Such a mechanism could bring together evidence from multiple risk factors and genetic vulnerabilities to form a convergent pathway in disease pathophysiology.